The levels of anti-HPV16/18 and anti-HPV31/33/ 35/45/52/58 antibodies among AS04-adjuvanted HPV16/18 vaccinated and non-vaccinated Ugandan girls aged 10–16 years - Nakalembe, Miriam; Banura, Cecily; Namujju, Proscovia B; Mirembe, Florence M (Infectious Agents and Cancer, 2014)
Abstract Background: Data on Human Papilloma virus (HPV) vaccine immune response in sub-Saharan Africa is still sparse yet such knowledge is critical for optimal implementation and monitoring of HPV vaccines. Our primary objective was to evaluate levels of anti-HPV-16/18 antibodies and six other ‘high risk’ HPV (hrHPV) types among the vaccinated and unvaccinated Ugandan girls. Methods: We conducted a cross sectional study among AS04-adjuvanted HPV-16/18 vaccinated and unvaccinated school girls aged 10–16 years in Western Uganda using purposive sampling. The vaccinated girls were at 18 months post vaccination. After consenting and assenting, data was collected using interviewer administered questionnaires for demographics and sexual history. Blood was drawn from which serum samples were analysed by the multiplex HPV serology technology to determine anti-HPV antibody levels to HPV-16/18 and six other hrHPV types (31, 33, 35, 45, 52 and 58). The antibody levels were expressed as Median Fluorescent Intensity (MFI). A total of 207 vaccinated [mean age 13.1 years (SD 1.5); range 10-16 years] and 197 unvaccinated girls [mean age 13.6 years (SD 1.3); range 10-16 years] participated in the study. Sexual activity was self reported among 14/207 (6.8%) vaccinated and 5/197 (2.5%) unvaccinated girls. The MFI levels for HPV-16 and HPV-18 were 15 and 20 times higher respectively in the vaccinated girls than in the unvaccinated girls. HPV-16 mean MFI level was 4691 (SD 1812; 95% CI: 4438-4958) among the vaccinated compared to 218 (SD 685; 95% CI: 190-252) among the unvaccinated girls. For HPV-18 the mean MFI level was 1615 (SD 1326; 95% CI: 1470-1776) among the vaccinated compared to MFI 103 (SD 506; 95% CI: 88 -121) among unvaccinated girls. In addition antibody levels to non vaccine hrHPV types (31, 33, 35, 45, 52 and 58) were all significantly higher in the vaccinated group than in the unvaccinated group (p<0.01). Conclusion: The AS04-Adjuvanted HPV-16/18 vaccinated girls showed a higher level of antibodies to HPV-16/18 and other non-vaccine hrHPV types compared to the unvaccinated girls. This may translate into protection against HPV-16/18 and other hrHPV types. Keywords: Human Papilloma Virus, Bivalent HPV vaccine, Immune response, Uganda, Adolescents
Keywords: anti-HPV16/18; anti-HPV31/33/ 35/45/52/58; antibodies; vaccinated and non-vaccinated; AS04-adjuvanted HPV16/18; Ugandan girls aged 10–16 years